Enhancement of the solubility and antioxidant capacity of α-linolenic acid using an oil in water microemulsion. Issue 8 (13th July 2017) - Chen, Boru; Hou, Mengna; Zhang, Bo; Liu, Tiankuo; Guo, Yun; Dang, Leping; Wang, Zhanzhong
Abstract : The present study was performed to enhance the solubility and antioxidant capacity of α-linolenic acid using an O/W microemulsion. Abstract : The applications of α-linolenic acid (ALA) in the food industry are restricted due to its poor water solubility and antioxidant stability. This study concentrates on developing an ALA-loaded microemulsion (ALA-ME) to enhance its solubility and antioxidant capacity. The formulation of the microemulsion was investigated based on pseudoternary phase diagrams. The ALA-ME was characterized by using electrical conductivity, viscosity and transmission electron microscopy (TEM). The microstructure of the ALA-ME was probed using nuclear magnetic resonance ( 1 H-NMR). The results proved that ALA-ME consisted of spheroidal droplets with 20–40 nm diameter. A structural transformation from water in oil (W/O) to oil in water (O/W) occurred, as seen from the electrical conductivity determination. The 1 H-NMR results revealed a transition of the ALA position encapsulated from the core area of the microemulsion to the lipophilic layer of the surfactant. Furthermore, two microstructural models of ALA-ME were proposed. The antioxidant evaluation demonstrated that the ALA antioxidant capacity in microemulsions was enhanced to about 80% compared with that of ALA in oil solution.